Multi‐Stakeholder Initiatives for Sustainable Development Goals: The Importance of Interlocutors. (28th February 2017) - Fowler, Alan; Biekart, Kees
Summary: This article argues that the complex multi‐stakeholder arrangements anticipated for implementing Sustainable Development Goals call for a distinct type of host: an interlocutor. This central idea arises from new comparative research on multi‐stakeholder initiatives (MSIs) undertaken in four countries: Costa Rica, Indonesia, Kenya and Kyrgyzstan. This work adds a detailed dimension to meta‐studies on conditions for success and practical guides for establishing and running MSIs. It begins to fill a significant gap in knowledge by analysing the attributes and competencies required for effectively orchestrating MSIs as well as illuminating their relative significance over time. The context is an anticipated expansion in demand for finely tuned and skilled hosting of Sustainable Development Goals‐inspired MSIs. This task will probably be more complicated than MSIs associated with climate change and Millennium Development Goals, both of which saw business on the side lines with uneven attention paid to the principle of local ownership. Recognising and investing in interlocution as a pivotal role can increase the performance of internationally inspired MSIs which, to date, have a mixed but generally poor record of effectiveness. © 2017 The Authors Public Administration and Development Published by John Wiley & Sons Ltd.